Clinical and epidemiological factors associated with residual lithiasis among patients who underwent laser lithotripsy - Velázquez-Guerrero, Saul E. (2024)
Objective: To evaluate the clinical and epidemiological factors associated with residual lithiasis among patients who underwent flexible ureteroscopy with laser lithotripsy (FURSLL). Materials and methods: An observational, analytical, retrospective and cross-sectional study, using a non-probability sampling method through consecutive case series. Demographic and clinical variables were collected from the medical records of patients who underwent FURSLL. Descriptive statistics, including measures of central tendency and dispersion, were applied. Pearson’s chi-square test and Fisher’s exact test were used to assess the associations, with statistical significance set at p ≤ 0.05. Results: A total of 24 medical records from patients with nephrolithiasis who underwent FULL were analyzed. The sample consisted of eight males (33.33 %) and 16 females (66.70 %), with a mean body mass index (BMI) of 30.8 ± SD 6.2 kg/m2. Comorbidities included diabetes mellitus in five (20.83 %), systemic hypertension in eight (33 %), obesity in nine (37.50 %) and chronic kidney disease in two (8.33 %) patients. The stones were located in the renal pelvis in 11 cases (45.80 %), followed by five cases (20.80 %) in the lower calyx, four cases (16.70 %) in multiple sites, three cases (12.50 %) in the middle calyx and one case (4.20 %) in the upper calyx. Fisher’s exact test showed an association between renal surgery and residual lithiasis after FURSLL (p = 0.038) (p ≤ 0.05). A similar association was observed when stone sizes were dichotomized into two categories (≤ 20 mm and ≥ 21 mm). Using Pearson’s chi-square test, stone size was also found to be associated with residual lithiasis (p = 0.017) (p ≤ 0.05). Conclusions: Stone size and a history of renal surgery are factors associated with residual lithiasis following FURSLL among patients diagnosed with nephrolithiasis.